Designing a Smart Farming Greenhouse Electrical Power Monitoring System Based on Internet of Things Technology - Sari, Marti Widya; Hardyanto, R. Hafid; Ciptadi, Prahenusa Wahyu; Kurniawan, Endi; Santoso, Banu (Engineering, Technology & Applied Science Research, 2026)
This study aimed to design and implement an Internet of Things (IoT)-based electrical power monitoring system to support energy-efficient operations in a solar-powered smart farming greenhouse. The proposed system integrates key hardware components, including a NodeMCU ESP8266 microcontroller, an ACS712-05A current sensor, and a ZMPT101B voltage sensor, to measure voltage, current, and power consumption in real time. The collected data are transmitted over Wi-Fi to the Firebase Realtime Database and visualized through an Android application equipped with real-time monitoring, historical logging, and energy cost estimation features. The experimental evaluation conducted between February and April 2025 assessed sensor accuracy and overall system reliability. The results show that the voltage sensor maintained stable performance with a maximum deviation of 0.5 V, while the current sensor recorded minor discrepancies of up to 0.5 A, largely influenced by network latency and environmental interference. These quantitative findings confirm the feasibility of using low-cost IoT sensors for continuous electrical monitoring in greenhouse environments. The main contribution of this research is the development and validation of an integrated IoT-based electrical monitoring framework that enhances transparency, supports data-driven decision-making, and promotes sustainable energy management in modern smart farming systems.